Coronary Artery Bypass Surgery [CABG] Perspective Past, Present and Future - Suraj Wasudeo Nagre (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2017)
The future of cardiac surgery seems to be in dark because of improved health awareness in public and improved cardiac Cath quality stents. I am discussing in my editorial how the cardiac surgery has evolved from nowhere to everywhere. But as there are ups there are downs also. The downward phase of cardiac surgery has started and now only we has to act otherwise we again go back to nowhere. Coronary artery disease has been termed as bread and butter of the cardiac surgeons. The disease has been managed since as early as 19th century and has seen many landmarks. Coronary artery disease is one of the important cause of death. Out of the organs whose failure can result into death, heart holds a special position as the defect responsible can be surgically corrected .Since coronary artery disease is one of the major causes afflicting the heart, hence coronary bypass holds a significant position. Coronary bypass was started by Favalaro in 1969.Since then the surgery has seen many improvements and from being done on pump in beginning but nowadays it is being done off pump mostly.